Diagnostics of low-pressure hydrogen discharge created in a 13.56 MHz RF plasma reactor. (27th June 2016) - Krištof, J; Annušová, A; Anguš, M; Veis, P; Yang, X; Angot, T; Roubin, P; Cartry, G
Abstract: A 13.56 MHz RF discharge in hydrogen was studied within the pressure range of 1–10 Pa, and at a power range of 400–1000 W. The electron energy distribution function and electron density were measured by a Langmuir probe. The gas temperature was determined by the Fulcher- α system in pure H2, and by the second positive system of nitrogen using N2 as the probing gas. The gas temperature was constant and equal to 450 ± 50 K in the capacitively coupled plasma (CCP) mode, and it increased with pressure and power in the inductively coupled plasma (ICP) mode. Also, the vibrational temperature of the ground state of hydrogen molecules was determined to be around 3100 and 2000 ± 500 K in the ICP and CCP mode, respectively. The concentration of atomic hydrogen was determined by means of actinometry, either by using Ar (5%) as the probing gas, or by using H2 as the actinometer in pure hydrogen (Q1 rotational line of Fulcher- α system). The concentration of hydrogen density increased with pressure in both modes, but with a dissociation degree slightly higher in the ICP mode (a factor 2).